Study on Synthesis of Solid Acid Catalyst from Borassus flabellifer L. Waste with Sulfonation Method: Kajian Sintesis Katalis Asam Padat dari Limbah Sabut Siwalan (Borassus flabellifer L.) dengan Metode Sulfonasi - Kurniati, Yuni; Prasetya, Fandi Angga; Hanafi, Fathur Iqbal; Taufik, Nugroho Muchamad; Arifiyana, Djamilah (Akademi Farmasi Surabaya, 2021)
Fiber of Borassus flabellifer L. includes agricultural wastes which containing lignocellulose components (hemicellulose and lignin) and high carbohydrate content. Siwalan coir fiber is quite potential to be used as a substrate in producing catalysts. Acid catalyst is one type of catalyst that as an important role in chemical process. This study aims to study the effect of the optimum mass ratio of carbon-KOH in the process of graphite synthesis based on siwalan charcoal so as to produce graphite with the most optimal characteristics, and optimum calcination temperature as a physical activation process in the synthesis of graphite based on siwalan coir fiber charcoal, and determine the time sulfonation which is optimum in producing acid catalysts There are 2 variables used in this study, temperature and sulfonation time. The method of making carbon is done by calcining to decompose the carbon source so that the composition is made according to what has been varied. After forming carbon-KOH composite, then sulfonation is carried out using sulfuric acid. The last step is to carry out the esterification step The process in this study discusses carboxylic acid, WCO (Cooking Oil Waste) and methanol (alcohol group).